Implementasi Model PBL, STAD, dan Make A Match Meningkatkan Aktivitas dan Hasil Belajar Matematika SDN Belitung Selatan 5 - Nurhidayah; Herti Prastitasari (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Problem on study This that is activity And results Study student low. Describe teacher activity, analyzing activity students, and results Study student is objective from study This . Research conducted​ use approach qualitative And Study Action Classes (PTK) conducted in 4 meetings . Study This use sheet observation And test written For analyze data. From the results research, teacher activity is obtained score 27 in the encounter First increase become score 39 in the meet fourth. Activity student meeting First reached 50%, increased to 100% on meeting fourth. The cognitive learning outcomes of the first meeting reached 41%, increasing in the fourth meeting to 95%, the affective aspect meeting First reaching 45% increased at the fourth meeting to 100%, and psychomotor aspects at the meeting First reached 41%, increasing in the fourth meeting to 100%. It can be concluded that the combination of the PBL, STAD, and Make A Match models can be implemented effectively and allows students to follow the learning process well , resulting in enhancement on activities and mathematics learning outcomes student. Suggestions for Principals, teachers and other researchers can use these learning models as references to improve quality education and quality learning at school.